Development of a care system for stroke patients with community participation in Bansog Subdistrict, Khonsawan District, Chaiyaphum Province - Hirungerd, Suptawee; Saenloa, Pornphattra; Thongsawang, Kamonrat (Thai Journal of Nursing, 2021)
The objectives of this participatory action research were 1) to develop a care system for stroke patients with community participation and 2) to evaluate the effectiveness of the care system for stroke patients with community participation. The participants consist of 1) two registered- nurses and public health technical officers, 2) twenty-seven village volunteers and heads of the villages, 3) thirty-six caregivers, and 4) thirty-seven stroke patients. This research consisted of three phases, including phase 1: situation analysis, phase 2: development of a care system for stroke patients with community participation, and phase 3: evaluation of the effectiveness of the care system for stroke patients. The instruments composed of the patient care work instruction and activities of daily living, satisfaction with care systems, personal data, heath, and assessment tools. Content analysis was used for qualitative data. Descriptive statistics and t-test were used in data analysis. The results revealed that the caring system for stroke patients increased community participation in planning, implementation, and evaluation. In addition, the average score of patients’ activities of daily living and caregivers’ satisfaction with the care systems after implementation of the care system was significantly higher than before using the care system at p < .05.